Corporate Governance in Companies with State Participation - K. P. Kharchilava; A. Yu. Bottaev (Управление)
In modern conditions the ongoing development of corporate governance in our country due to several factors. First of all, the Russian economy is increasingly involved in the economic processes of globalization, increased interaction of large Russian companies with the global financial market. In addition, Russia’s largest company significantly expanded its international activities, including through the acquisition of foreign assets. Joint-stock medium-sized companies have realized the need to attract external financing through the search for a strategic investor or access to stock markets. Significant changes made to the corporate legislation.